Where is the greatest impact of uncontrolled HIV infection on AIDS and non-AIDS events in HIV?. (14th January 2018) - Mocroft, Amanda; Laut, Kamilla; Reiss, Peter; Gatell, Jose; Ormaasen, Vidar; Cavassini, Matthias; Hadziosmanovic, Vesna; Mansinho, Kamal; Pradier, Christian; Vasylyev, Marta; Mitsura, Victor; Vandekerckhove, Linos; et al.
Abstract : Objective: The extent to which controlled and uncontrolled HIV interact with ageing, European region of care and calendar year of follow-up is largely unknown. Method: EuroSIDA participants were followed after 1 January 2001 and grouped according to current HIV progression risk; high risk (CD4 + cell count ⩽350/μl, viral load ≥10 000 copies/ml), low risk (CD4 + cell count ≥500 cells/μl, viral load <50 copies/ml) and intermediate (other combinations). Poisson regression investigated interactions between HIV progression risk, age, European region of care and year of follow-up and incidence of AIDS or non-AIDS events. Results: A total of 16 839 persons were included with 136 688 person-years of follow-up. In persons aged 30 years or less, those at high risk had a six-fold increased incidence of non-AIDS compared with those at low risk, compared with a two-to-three-fold increase in older persons ( P  = 0.0004, interaction). In Eastern Europe, those at highest risk of non-AIDS had a 12-fold increased incidence compared with a two-to-four-fold difference in all other regions ( P  = 0.0029, interaction). Those at high risk of non-AIDS during 2001–2004 had a two-fold increased incidence compared with those at low risk, increasing to a five-fold increase between 2013 and 2016 ( P  < 0.0001, interaction). Differences among high, intermediate and low risk of AIDS were similar across age groups, year of follow-up and Europe ( P  = 0.57, 0.060 and 0.090, respectively, interaction). Conclusion: Factors other than optimal control of HIV become increasingly important with ageing for predicting non-AIDS, whereas differences across Europe reflect differences in patient management as well as underlying socioeconomic circumstances. The differences between those at high, intermediate and low risk of non-AIDS between 2013 and 2016 likely reflects better quality of care.